Placebo Effects in Psychotherapy: A Framework - Enck, Paul; Zipfel, Stephan (Frontiers in Psychiatry, 2019)
The issue of placebo response and the extent of its effect on psychotherapy is complex for two specific reasons: i) Current standards for drug trials, e.g. true placebo interventions, double-blinding, cannot be applied to most psychotherapy techniques, and ii) some of the "non-specific effects" in drug therapy have very specific effects in psychotherapy, such as the frequency and intensity of patient-therapist interaction. In addition, different psychotherapy approaches share many such specific effects (the "dodo bird verdict") and lack specificity with respect to therapy outcome. Here, we discuss the placebo effect in psychotherapy under four aspects: a) non-specific factors shared with drug therapy (context factors); b) non-specific factors shared among all psychotherapy traditions (common factors); c) specific placebo control options with different psychotherapy modalities; and d) non-specific control options for the specific placebo effect in psychotherapy. The resulting framework proposes that the exploration and enumeration of context factors, common factors, and specific factors contributes to the placebo effects in psychotherapy.